Leveraging The Animated Video Ibra Berkisah To Prevent Bullying In Early Childhood (PIAUD IAIN Kudus, 2024)
To prevent bullying in early childhood, it is crucial to introduce children to the impacts of bullying from an early age. As a widely popular platform among children, YouTube can serve as an effective medium for educating them about the consequences of bullying. This research explores how the animated video “Ibra Berkisah,” mainly the episode titled “Bully,” can be used as an educational tool to prevent bullying in early childhood. The study adopts a qualitative descriptive design, which is well-suited for investigating and understanding the animated video “Ibra Berkisah” application in addressing bullying behaviors among young children. Data collection methods likely include observations, interviews, and documentation to evaluate the video’s effectiveness in teaching anti-bullying values. The study involved 26 kindergarten children as participants. The findings indicate that the children could identify bullying behaviors and take proactive steps to prevent such actions in their interactions. The results suggest that the animated video “Ibra Berkisah” is highly suitable for early childhood audiences, as it conveys numerous moral messages in a manner that is easy for children to understand. The video’s engaging format and straightforward narrative make it accessible and appealing, enhancing its effectiveness as an educational tool.